Amtsāl Al-Qur’an Sebagai Sarana Pendidikan Nilai Sosial dan Empati - Furqan Firmansyah; Antoni; Misnawati (AL-MIKRAJ Jurnal Studi Islam dan Humaniora (E-ISSN 2745-4584), 2025)
This study aims to examine amtsāl Al-Qur’an as a Qur’anic stylistic device and to analyze its pedagogical relevance in educating social values and empathy within Islamic Religious Education. Using a qualitative, library-based approach, the study explores the definitions of amtsāl and the Qur’an, outlines the main types of amtsāl (muṣarraḥah, kāminah, and mursalah) with representative verses, and discusses the wisdoms underlying their use. The findings indicate that amtsāl functions not only as a rhetorical tool that clarifies abstract concepts, but also as a powerful pedagogical instrument for shaping social character. Through parables that engage both cognition and emotion, the Qur’an cultivates solidarity, social responsibility, care for others, and respect for human dignity, as reflected in Q.S. al-Ḥashr 9 and Q.S. al-Mā’idah 32. Thus, amtsāl Al-Qur’an can serve as a contextual learning strategy aimed at fostering character and empathy